Enhanced photovoltaic effects in A-site samarium doped BiFeO3 ceramics: The roles of domain structure and electronic state. Issue 5 (April 2016) - Tu, Chi-Shun; Chen, Cheng-Sao; Chen, Pin-Yi; Wei, Hsiu-Hsuan; Schmidt, V.H.; Lin, Chun-Yen; Anthoniappen, J.; Lee, Jenn-Min
Abstract: This work reports enhanced photovoltaic (PV) responses of (Bi1 −  x Sm x )FeO3 ( x  = 0.0, 0.05, 0.10) ceramics (BFO100 x Sm) with ITO film under near-ultraviolet irradiation (λ = 405 nm). The ceramics were characterized by micro-Raman scattering, high-resolution transmission electron microscopy, and synchrotron X-ray absorption spectroscopy (XAS). A rhombohedral R 3 c symmetry with tilted FeO6 octahedra has been confirmed. The Fe K -edge absorption spectra reveal a slight shift toward higher energy as A-site Sm 3+ substitution increases. The oxygen K -edge XAS reveals an enhancement of hybridization between the O 2 p and unoccupied Fe 3 d states due to Sm doping. The optical band gaps are in the range of 2.15–2.24 eV. The maximal PV power-conversion and external quantum efficiencies respectively reach 0.37% and 4.1% in the ITO/BFO5Sm/Au heterostructure. The PV responses can be described quantitatively by a p - n -junction-like model. The domain structures and hybridization between the O 2 p and Fe 3 d states play important roles for the PV responses.